The development of undergraduate students’ concepts about the fanfictional genre system (Polifonia, 2020)
The fanfictional genre has not been extensively investigated in Brazil. In fact, there is very little academic work on this genre in universities (MYERS, 2006, MORLEY, 2007, BLYTHE & SWEET, 2008, HEALEY, 2009 and OBERHOLZER, 2014). Therefore, a Fanfictional Creative Writing in English course (FCWE) was developed and taught at the end of 2016. This course was attended by 5 undergraduate students in Languages and Literatures. Two of the objectives of this course were to 1) identify and 2) develop concepts about fanfictions. For this article, only student A was taken as an example. The methodology applied was the Case Study (DUFF, 2008, 2012; DYSON, 2005; STAKE, 2006). The FCWE course was based on the Vygotskian sociocultural theory (VYGOTSKY, 2004; 2007). As a result, student A demonstrated signs of development regarding social facts, speech acts, genre sets, and genre systems (BAZERMAN, 2012; CURRY & LILLIS, 2016).